A Comparative Analysis of Rectangular Water Tank with and Without Earth Pressure (Staad) - Abhilash Sautkar; Pradeep Kumar Nirmal; Pratik Kathale (International Journal of Scientific Research in Civil Engineering, 2025)
This approach has a number of benefits over traditional manual computations. STAAD Pro streamlines the analytical process, enabling effective consideration of complex geometries and a range of loading conditions. The program's visualization functions provide clear graphical representations of stress and deformation patterns, allowing for a comprehensive understanding of the tank's structural behavior. Additionally, STAAD Pro's iterative design optimization function allows engineers to explore several tank designs and material properties, assisting them in creating a cost-effective and safe design that meets all project requirements. To sum up, STAAD Pro is a helpful tool for structural engineers to analyze rectangular water tanks. It ensures the dependability and safety of these essential water storage facilities and promotes efficient design techniques.
Keywords: Rectangular Water Tank; Earth pressure; seismic analysis; Staad Pro